Effects of Lactobacillus gasseri OLL2716 on Helicobacter pylori-Associated Dyspepsia: A Multicenter Randomized Double-Blind Controlled Trial. (11th July 2016) - Takagi, Atsushi; Yanagi, Hidetaka; Ozawa, Hideki; Uemura, Naomi; Nakajima, Shigemi; Inoue, Kazuhiko; Kawai, Takashi; Ohtsu, Toshihiro; Koga, Yasuhiro
Abstract : Some Lactobacillus spp. suppress Helicobacter pylori in the stomach and have potential therapeutic applications for the treatment of gastrointestinal conditions. In this study, the effects of Lactobacillus strains on functional dyspepsia associated with H. pylori infection were examined. Volunteers were screened using the 13 C-urea breath test (UBT) and H. pylori stool test, and 131 participants who met the selection criteria (mean age: 48.9 years) were randomly given L. gasseri OLL2716-containing yogurt or placebo yogurt once daily for 12 weeks. Gastrointestinal symptoms (epigastric pain, bloating, postprandial fullness, nausea, and heartburn) and the levels of serum pepsinogen (PG), 13 C-UBT, and H. pylori stool antigen were assessed. No significant differences were observed between the groups in UBT results, H. pylori stool antigens, or the serum PGI/II ratio. In the L. gasseri group, postprandial fullness was significantly lower at the end of the trial compared to the initial level (p < 0.05 ) and significantly fewer patients had a VAS score of >10 for bloating compared to the placebo group (p < 0.05 ). Dietary supplementation with L. gasseri OLL2716-containing yogurt may effectively suppress dyspeptic symptoms in H. pylori -infected patients. This study was registered at the University Hospital Medical Network Clinical Trial Registry (UMIN000016746 ).